A bioethical approach: vegan and vegetarian experiences - Tunçay, Güzin Yasemin; Bulut, Meryem (Progress in Nutrition, 2019)
Veganism and vegetarianism are bioethical approaches as well as lifestyles and philosophies of life. There may be more than one reason why people choose to be a vegan/vegetarian. They can be discussed in terms of ethics, animal rights, respect for sentient beings, ecology and violence. In this study, veganism/vegetarianism is discussed in detail in terms of bioethics. A qualitative research was performed by using the snowball or chain sampling method and 40 people older than 18 years old and vegan/vegetarian for at least two months were interviewed. The interviews were conducted face-to-face with each participant from June 20 to October 24 in 2015. The data gathered in the study were evaluated in accordance with content analysis. Responses to open–ended questions were coded. Emerging themes were discussed and appropriate suggestions were made. The results of the study revealed reasons for adopting veganism/vegetarianism, ease and difficulties and benefits and harmful effects of these life-styles. It was concluded that veganism and vegetarianism could be dealt with in terms of bioethics.